2007
DOI: 10.2460/javma.231.7.1061
|View full text |Cite
|
Sign up to set email alerts
|

Results of the veterinary enalapril trial to prove reduction in onset of heart failure in dogs chronically treated with enalapril alone for compensated, naturally occurring mitral valve insufficiency

Abstract: Chronic enalapril treatment of dogs with naturally occurring, moderate to severe MR significantly delayed onset of CHF, compared with placebo, on the basis of number of CHF-free days, number of dogs free of CHF at days 500 and study end, and increased time to a combined secondary endpoint of CHF-all-cause death. Improvement in the primary endpoint, CHF-free survival, was not significant. Results suggest that enalapril modestly delays the onset of CHF in dogs with moderate to severe MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 44 publications
9
141
1
2
Order By: Relevance
“…Several studies have reported efficacy of ACEI drugs in the management of dogs with heart disease associated with MMVD. Two clinical trials designed to determine whether treatment with enalapril would prevent or delay onset of CHF in small breed dogs with MMVD reported limited12 benefit or lack of clinical effect 13. Benazepril used alone or as an add‐on to standard treatment in MMVD or DCM dogs with CHF extended life span compared to dogs that did not receive benazepril 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported efficacy of ACEI drugs in the management of dogs with heart disease associated with MMVD. Two clinical trials designed to determine whether treatment with enalapril would prevent or delay onset of CHF in small breed dogs with MMVD reported limited12 benefit or lack of clinical effect 13. Benazepril used alone or as an add‐on to standard treatment in MMVD or DCM dogs with CHF extended life span compared to dogs that did not receive benazepril 34.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial data are limited in dogs, and the majority of studies have focused on treatment to manage chronic myxomatous valvular disease (MMVD). Trials using enalapril and conducted largely in populations of dogs with advanced heart disease but not heart failure have reported limited benefit or no benefit in these populations 12, 13. Digitalis traditionally has been used to manage supraventricular tachyarrhythmias14 and dilated cardiomyopathy in dogs,14, 15, 16 but evidence for clinical efficacy is sparse.…”
mentioning
confidence: 99%
“…The above drugs may ameliorate clinical signs and improve both quality and quantity of life in symptomatic but not asymptomatic canine MVD [3,13,17]. Thus, precise evaluation and staging of dogs with MVD is mandatory before administering any therapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus for this group of patients regarding whether or not a therapy might be beneficial. Two studies showed that long-term treatment with enalapril in asymptomatic dogs with MVD and MR did not or modestly delayed the onset of heart failure regardless of whether or not cardiomegaly was present at initiation of the study (27,28). Despite the lack of consensus, some use angiotensin-converting enzyme inhibitors (ACE-I) in this period of the disease, as it was shown in some studies in dogs and people to have some beneficial effect (28,29).…”
Section: Pharmacological Management Of Mmvdmentioning
confidence: 99%